2017
DOI: 10.1016/j.diabet.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical inertia and its impact on treatment intensification in people with type 2 diabetes mellitus

Abstract: Many people with type 2 diabetes mellitus (T2DM) fail to achieve glycaemic control promptly after diagnosis and do not receive timely treatment intensification. This may be in part due to 'clinical inertia', defined as the failure of healthcare providers to initiate or intensify therapy when indicated. Physician-, patient- and healthcare-system-related factors all contribute to clinical inertia. However, decisions that appear to be clinical inertia may, in fact, be only 'apparent' clinical inertia and may refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
172
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(189 citation statements)
references
References 91 publications
1
172
0
3
Order By: Relevance
“…Clinical inertia, defined as failure to intensify anti‐hyperglycaemic therapy in a timely manner, has been proposed as one explanation for these findings when sequential therapy is used. Although many factors contribute to clinical inertia, this traditional sequential treatment paradigm for type 2 diabetes, comprising stepwise addition of anti‐hyperglycaemic agents to initial metformin monotherapy in response to increased glycated haemoglobin (HbA1c) levels, may be a major reason why some patients experience delays in reaching their glycaemic goals …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical inertia, defined as failure to intensify anti‐hyperglycaemic therapy in a timely manner, has been proposed as one explanation for these findings when sequential therapy is used. Although many factors contribute to clinical inertia, this traditional sequential treatment paradigm for type 2 diabetes, comprising stepwise addition of anti‐hyperglycaemic agents to initial metformin monotherapy in response to increased glycated haemoglobin (HbA1c) levels, may be a major reason why some patients experience delays in reaching their glycaemic goals …”
Section: Introductionmentioning
confidence: 99%
“…clinical inertia, 4 this traditional sequential treatment paradigm for type 2 diabetes, comprising stepwise addition of anti-hyperglycaemic agents to initial metformin monotherapy in response to increased glycated haemoglobin (HbA1c) levels, may be a major reason why some patients experience delays in reaching their glycaemic goals. [5][6][7] An alternative approach to type 2 diabetes treatment is simultaneous combination therapy with anti-hyperglycaemic agents that have complementary mechanisms of action, and therefore target multiple physiological defects.…”
mentioning
confidence: 99%
“…Despite these recommendations, clinical inertia, defined as the failure to intensify treatment when required, is common in clinical practice in patients with T2D . In a UK study of patients treated with basal insulin who were clinically eligible for treatment intensification, only 31% had their treatment intensified, with a median time to intensification of 3.7 years .…”
Section: Introductionmentioning
confidence: 99%
“…7 Despite these recommendations, clinical inertia, defined as the failure to intensify treatment when required, is common in clinical practice in patients with T2D. [10][11][12][13][14][15][16][17] In a UK study of patients treated with basal insulin who were clinically eligible for treatment intensification, only 31% had their treatment intensified, with a median time to intensification of 3.7 years. 11 Delay in treatment intensification in patients with uncontrolled T2D has been shown to have a number of clinical consequences, including a significantly increased risk of myocardial infarction, heart failure, stroke, and a composite endpoint of cardiovascular events, 18 as well as a higher incidence of (and significantly shorter median time to) progression of diabetic retinopathy.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the recommendations for strict glucose control, numerous studies have shown that increased HbA 1c levels may persist for long periods of time in patients with T2DM [8,9]; these findings likely reflect the progressive nature of the disease but are also attributed to 'clinical inertia' which is defined as a failure to 'intensify therapy when indicated, or a failure to act despite recognition of the problem' [10]. Clinical inertia in the management of patients with T2DM may result in suboptimal glycaemic control, which is associated with increased incidence of cardiovascular events [11].…”
Section: Introductionmentioning
confidence: 99%